The first omen [videorecording (DVD)] - Stevenson, Arkasha; Smith, Tim (Screenwriter); Thomas, Keith, 1975-; Jacoby, Ben; Korven, Mark; Free, Nell Tiger, 1999-; Ineson, Ralph, 1969-; Braga, Sonia, 1950-; Barhom, Tawfeek; Caballero, María, 1994-; Dance, Charles; Nighy, Bill, 1949-; et al. (20th Century Studios, 2024)
When a young American woman is sent to Rome to begin a life of service to the church, she encounters a darkness that causes her to question her own faith and uncovers a terrifying conspiracy that hopes to bring about the birth of evil incarnate.